Hunger and satiety: neuronal dynamics in Hydra behavior - Holstein, Thomas W. (Cell reports, 2024)
Hormonal and neuronal inputs to the brain control how much animals eat. The origins of this behavior were unclear, but in this issue of Cell Reports, Giez et al.1 describe specific neurons inhibiting feeding in evolutionary ancient animals without brain.